3D numerical simulation of heat transfer during dry drilling of Inconel 718. (April 2021) - Chenegrin, Kévin; Roux, Jean-Christophe; Helfenstein-Didier, Clémentine; Pouvreau, Cédric; Girinon, Mathieu; Karaouni, Habib; Bergheau, Jean-Michel; Feulvarch, Eric
Abstract: The aim of this paper is to compute heat transfer as a function of drilling parameters with a relatively short computing time. Assuming that the geometry of the chips close to the cutting edges of the drill tool is almost the same throughout the drilling operation, a numerical strategy is developed in the second section in order to create analytically the geometry of the chips by means of the process parameters and the geometry of the drill tool. An efficient identification procedure is then presented to model the material flow. In the third section, an experimental device is detailed as well as its tomography geometrical analysis after drilling. A simple calibration strategy is developed in order to estimate the Taylor-Quinney coefficient and the thermal impact of the removal material on the hole surface. Then, an application is detailed to show the capability of the modeling proposed to simulate the temperature variation in the case of a large depth hole.